A broadband dual‐polarized multi‐dipole antenna fed by coplanar stripline. Issue 8 (15th June 2018) - Chen, Yanzheng; Lin, Wenbin; Liao, Cheng; Kan, Guojin; Raza, Ali
Abstract: A simple wideband dual‐polarized multi‐dipole antenna fed by coplanar stripline is proposed in this article. An enhanced impedance bandwidth of about 43.5% is achieved with this antenna for VSWR < 1.5 and gain > 8 dBi at 2 ports, covering the operating frequency region from 1.69 to 2.63 GHz. The radiation pattern is measured and 3‐dB beamwidths of 64 ± 3 degree at E‐plane and 54 ± 6 degree at H‐plane for port 1 and 65 ± 4 degree at E‐plane and 54 ± 5 degree at H‐plane for port 2 are acquired. The port‐to‐port isolation is above 25 dB. This model has been manufactured and measured. The experimental results show good amount of similarity with simulated ones.